Evaluation of Supplier Performance Effectiveness Measurement using the SCOR (Supply Chain Operations Reference) and ANP (Analytic Network Process) Method Approach (Case Study: Supply of Silica Powder to PT. Freeport Indonesia - Java Integrated and Industrial Port Estate (JIIPE), Gresik) - Samsir, Samsir; Gunarta, I Ketut (Journal of Applied Sciences, Management and Engineering Technology, 2024)
Companies must be able to provide quality products at relatively efficient prices and distribute them quickly to survive and excel in competition. Companies need to collaborate with various parties to innovate and create competitive advantages. Suppliers are essential actors as providers of resources that companies need precisely, quickly, and efficiently, so good supply chain management is required. Companies must be able to assess supplier performance appropriately because this is the key to the success of successful SCM. The object of this research was carried out at the company PT. Freeport Indonesia. This company experienced several problems related to the instability of the supply of silica powder as a reducing agent for copper ore, such as non-fulfilment of order quantities, delays, price changes and so on. This research aims to identify appropriate criteria related to supplier performance using the SCOR (Supply Chain Operations Reference) and ANP methods in the companies studied. From the results of this research, the best supplier criteria will be obtained based on quantitatively weighted classifications.